Smoothing Problem in Anticipating Scenario - Dorogovtsev A.A. (Український математичний журнал, 2005)
We consider a smoothing problem for stochastic processes satisfying stochastic differential equations with Wiener processes that may not have a semimartingale property with respect to the joint filtration. Розглядається задача інтерполяції для випадкових процесів, що задовольняють стохастичні диференціальні рівняння з вінеровими процесами, які не є семімартингалами відносно спільної фільтрації.